2014
DOI: 10.7717/peerj.560
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a truncated splice variant of IL-18 receptor alpha in the human and rat, with evidence of wider evolutionary conservation

Abstract: Interleukin-18 (IL-18) is a pro-inflammatory cytokine which stimulates activation of the nuclear factor kappa beta (NF-κB) pathway via interaction with the IL-18 receptor. The receptor itself is formed from a dimer of two subunits, with the ligand-binding IL-18Rα subunit being encoded by the IL18R1 gene. A splice variant of murine IL18r1, which has been previously described, is formed by transcription of an unspliced intron (forming a ‘type II’ IL18r1 transcript) and is predicted to encode a receptor with a tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…The iHS test, aimed at defining evidence of recent positive selection, detected selective sweeps for three tightly linked SNPs in the IL18R1 gene, which encodes a cytokine receptor from the interleukin 1 receptor family. It has been previously discussed that the conserved across evolutionary branches mechanism of regulating IL18 signaling might represent a target for selective pressure 40 . This assumption is consistent with the fact that the top IL18R1 SNP rs2001461 (iHS CEU score 4.54) was associated with the IL18R1 expression (GWAS trait P value = 3.00E−129).…”
Section: Discussionmentioning
confidence: 99%
“…The iHS test, aimed at defining evidence of recent positive selection, detected selective sweeps for three tightly linked SNPs in the IL18R1 gene, which encodes a cytokine receptor from the interleukin 1 receptor family. It has been previously discussed that the conserved across evolutionary branches mechanism of regulating IL18 signaling might represent a target for selective pressure 40 . This assumption is consistent with the fact that the top IL18R1 SNP rs2001461 (iHS CEU score 4.54) was associated with the IL18R1 expression (GWAS trait P value = 3.00E−129).…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that IL18 mediates its biological effects in a variety of organ systems and cell types 9 through stepwise binding to IL18R1 and IL18RAP, and subsequent juxtaposition of the intracellular toll/interleukin-1 receptor (TIR) domains of both receptors 50 . However, additional truncated variants of IL18R1 and IL18RAP, lacking this domain essential for recruitment of MYD88 adaptor protein and subsequent activation of (NF)-ΚΒ and MAPK pathways, have been reported in humans and rodents (arbitrary named type II receptors) 10 11 51 . Though their exact role is yet to be fully established, they are proposed to act as competitors of the canonical receptors in heterodimer formation thereby inhibiting IL18 actions 10 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Their function has not been clarified, and there is no information as to whether they are generated by alternative splicing or proteolytic cleavage. IL‐1R5 can undergo alternative splicings that generate soluble receptors in mice and rats and a non‐signaling membrane receptor, similar to IL‐1R2, in humans . Both sIL‐1R5 and sIL‐1R7, forming complexes with IL‐18, have been found at increased levels in the serum of patients with rheumatoid arthritis and adult‐onset Still's disease .…”
Section: Regulation In the Il‐1r Familymentioning
confidence: 99%
“…IL-1R5 can undergo alternative splicings that generate soluble receptors in mice and rats and a non-signaling membrane receptor, similar to IL-1R2, in humans. 380,381 Both sIL-1R5 and sIL-1R7, forming complexes with IL-18, have been found at increased levels in the serum of patients with rheumatoid arthritis and adult-onset Still's disease. 188 In mice, it has been shown that sIL-1R7 worsens experimental arthritis through upregulation of Th17 activation and concomitant downregulation of Th1, Th2, and Treg activity, 382 but whether this effect has anything to do with IL-18 inhibition is not known.…”
Section: Soluble Forms Of Il-1r5 and Il-1r7 The Receptor And Co-recementioning
confidence: 99%